THE ROLE OF THE GREEN ECONOMY IN INCREASING THE EFFICIENCY OF E-COMMERCE SERVICES: INTERNATIONAL EXPERIENCE AND PROSPECTS FOR UZBEKISTAN - Rajabov Jaxongir (Zamonaviy ilmiy yondashuvlar va texnologik taraqqiyotning ustuvor yo‘nalishlari, 2026)
This article examines the role and significance of green economy principles in improving the efficiency of e-commerce services. Based on international experience from China, the European Union, and South Korea, the economic benefits of integrating digital platforms with green logistics are analyzed. The study also considers the current situation, existing problems, and future prospects of Uzbekistan in this field. As a result of the research, practical recommendations were developed to strengthen the synergy between e-commerce and the green economy.